Safety, Tolerability, Efficacy and Logistics of Administration of Three Types of Therapeutic Feeds to Children with Severe Acute Malnutrition (SAM) - Sujata Saunik; Mrudula Phadke; Raji Nair; Jatin Khosla; Tarun Patel; Venkataraman R.; Singal V. (International Journal of Nutrition, 2018)
Objective: To analyse safety, tolerability, efficacy and logistic issues related to administration of 3 types of therapeutic feeds to children with severe acute malnutrition (SAM) from tribal district of Nandurbar, Maharashtra. Design: A three arm open label, block randomized trial using 3 therapeutic feeds i.e. commercially available ready to use therapeutic feed (C-RUTF), locally prepared ready to use therapeutic feed ( L-RUTF) & amylase rich food(ARF) was given to 1092 tribal children of SAM in Nandurbar District, Maharashtra, India during 2014-2015. Setting: Tribal district of Nandurbar, Maharashtra. Participants: 1092 children of SAM, 766 on C-RUTF, 184 on L-RUTF & 143 on ARF followed on treatment for 8 weeks. Outcomes: The recovery rates in the three groups, any untoward effects during treatment and logistic aspects of procurement, delivery, storage & administration of therapeutic feeds. Results: Total number of children with SAM were 1092. Gr 1 – Out of 765 children of SAM, 404 (52.8%) recovered on C-RUTF. Gr 2 – 80 (43.5%) recovered out of 184 on L-RUTF. Gr 3 – 64 (44.8%) recovered on ARF at the end of 8 weeks of treatment, the difference being statistically significant between C-RUTF & others. Out of 38 children on C-RUTF, it was observed that 1 had diarrhoea, 1 had vomiting, 1 had fever, 4 children reported more activity in terms of playfulness, more speaking & smiling. 31 children had nothing specific to report. Out of 34 children on L-RUTF, 6 children reported diarrhoea, 1 had vomiting & 4 children reported fever. 3 children reported more activity. 23 children had nothing specific to report. Out of 19 children on ARF, 1 had diarrhoea, 1 had vomiting, 1 had fever, 3 reported more activity. 13 had nothing specific to report. Untoward effects were noted in 3 out of 38 (7.89%) in C-RUTF group, 11 out of 34 (32.35%) in L-RUTF group and 3 out of 19 (15.7%) in ARF group. Conclusion: C-RUTF was found to be more efficacious, with least untoward effects, easy to administer and was more palatable when compared to L-RUTF & ARF.
Keywords: severe acute malnutrition